Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/s0197-3975(03)00058-4
|View full text |Cite
|
Sign up to set email alerts
|

From “contravention of laws” to “lack of rights”: redefining the problem of informal settlements in South Africa

Abstract: Informal urban land occupation in South Africa is treated in a technocratic manner, consistent with the policy of orderly urbanisation introduced in the 1980s. This approach focusses on the contravention of laws governing property and land use, and accordingly results in most cases in evictions and relocations. A new mandate of the national Department of Housing is to eradicate the phenomenon of urban informal settlements in the next 15 years. This mandate gives new justification to the deterministic approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…According to Hofmann et al (2008), informal settlements are defined (1) as areas where groups of housing units have been constructed on land that the occupants have no legal claim to or occupy illegally and (2) as unplanned settlements and areas where housing is not in compliance with the current planning and building regulations (unauthorized housing). Studies by Huchzermeyer (2004) and Richards et al (2006) have shown that in developing countries, informal urban areas are there to stay for the next decades and beyond.…”
Section: Challenges In the Informal Urban Areasmentioning
confidence: 99%
“…According to Hofmann et al (2008), informal settlements are defined (1) as areas where groups of housing units have been constructed on land that the occupants have no legal claim to or occupy illegally and (2) as unplanned settlements and areas where housing is not in compliance with the current planning and building regulations (unauthorized housing). Studies by Huchzermeyer (2004) and Richards et al (2006) have shown that in developing countries, informal urban areas are there to stay for the next decades and beyond.…”
Section: Challenges In the Informal Urban Areasmentioning
confidence: 99%
“…Political and residential changes have opened literal and figurative space for various kinds of urban encroachment, including the occupation of urban land for informal settlements (Saff, ; Huchzermeyer, ; Huchzermeyer & Karam, ) and the ‘hijacking’ of inner city residential buildings (Murray ; Wilhelm‐Solomon ). Lefebvre and Bayat have each been used to explain and agitate toward change in South African cities (Benson & Meyer, ; Cirolia et al ., ; Desai, ; Goebel, ; Huchzermeyer, ; Maharaj, ; Parnell & Pieterse, ; Pieterse, ; see Benit‐Gbaffou & Oldfield, on troubling the use of RttC) .…”
Section: Agonistic Transgression In South African Citiesmentioning
confidence: 99%
“…They would often say things like “I don’t want a boyfriend in Town Two” because “the old people will see” or “people will talk.” Life in a township has the potential to compromise both physical and social privacy (Huchzermeyer 2004; Amuyunzu-Nyamongo et al 2007). In Town Two, young women most often lived in households and even shared bedrooms with family members.…”
Section: The Meaning Character and Trajectory Of Sexual Partnershipsmentioning
confidence: 99%